Increasing systemic risk during the Covid-19 pandemic: A cross-quantilogram analysis of the banking sector - Eduard Baumöhl; Elie Bouri; Thi-Hong-Van Hoang; Syed Jawad Hussain Shahzad; Tomáš Výrost (ZBW – Leibniz Information Centre for Economics, 2020)
Over the last few decades, large banks worldwide have become more interconnected. As a result, the failure of one can trigger the failure of many. In finance, this phenomenon is often known as financial contagion, which can act like a domino effect. In this paper, we show an unprecedented increase in bank interconnectedness during the outbreak of the Covid-19 pandemic. We measure how extreme negative stock market returns from one bank can spill over to the other banks within the network. Our contribution relies on the establishment of a new systemic risk index based on the cross-quantilogram approach of Han et al. (2016). The results indicate that the systemic risk and the density of the spillover network among 83 banks in 24 countries have never been as high as during the Covid-19 pandemic – much higher than during the 2008 global financial crisis. Furthermore, we find that US banks are the most important risk transmitters, and Asian banks are the most important risk receivers. In contrast, European banks were strong risk transmitters during the European sovereign debt crisis. These findings may help investors, portfolio managers and policymakers adapt their investment strategies and macroprudential policies in this context of uncertainty.
Keywords: G01; G15; G21; G28; C21; 330; Systemic risk; Banks; Covid-19 pandemic; Cross-quantilogram; Financial networks